2023
DOI: 10.1002/ecs2.4489
|View full text |Cite
|
Sign up to set email alerts
|

Copepods' true colors: astaxanthin pigmentation as an indicator of fitness

Abstract: Pigmentation is often overlooked in zooplankton, since these organisms are mostly colorless to fit the translucid water medium. However, one of the dominant zooplankton taxa in aquatic ecosystems—copepods—often show a bright red‐orange or blue coloration owing to the accumulation of carotenoid pigments in some parts of their bodies. Even though there are many functional traits describing copepod's performance (e.g., size, feeding, and reproductive modes), it is surprising that the role of such a simple and vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 167 publications
(384 reference statements)
0
3
0
Order By: Relevance
“…This study showed that surface-dwelling copepods in the subtropical North Pacific have detectable levels of photoprotective compounds, although their concentrations vary among taxonomic groups. The range of mean carotenoid content (0.0148-0.0965 µg mg dry wt −1 ) in this study was lower than the median content in marine copepods (0.137 µg mg dry wt −1 ) (Vilgrain et al 2023). As for MAAs, to the best of our knowledge, this is the first study in the Pacific to report the MAA content in subtropical marine copepods, using adequate sampling procedures after gut evacuation, following a similar study in the Atlantic (Fileman et al 2017).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This study showed that surface-dwelling copepods in the subtropical North Pacific have detectable levels of photoprotective compounds, although their concentrations vary among taxonomic groups. The range of mean carotenoid content (0.0148-0.0965 µg mg dry wt −1 ) in this study was lower than the median content in marine copepods (0.137 µg mg dry wt −1 ) (Vilgrain et al 2023). As for MAAs, to the best of our knowledge, this is the first study in the Pacific to report the MAA content in subtropical marine copepods, using adequate sampling procedures after gut evacuation, following a similar study in the Atlantic (Fileman et al 2017).…”
Section: Discussioncontrasting
confidence: 76%
“…and Acrocalanus spp., had relatively high carotenoid contents. Although the function of carotenoid accumulation in copepods is still debated (Vilgrain et al 2023), its photoprotective role against reactive oxygen species produced by short-light radiation is well known (Hairston 1976). One well-known example is the blue pigmentation produced by carotenoids in neustonic pontellid copepods, which protects them from strong sunlight (Herring 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying transparency might give information about the organism's ecology (reproduction with gonads or eggs, feeding with guts content, Orenstein et al., 2022). Transparency and colour can also be related to physiological functions (Vilgrain et al., 2022), for example, carotenoids effects against oxidative stress (Brüsin et al., 2016), or possibly the utilization of pigmentation and DVM in order to escape visual predators (Hays et al., 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The trade-off between predation stress and copepod body colors has been noted in several studies 51 . Typically, highly pigmented copepods are more susceptible to predator detection in shallow waters 52 .…”
Section: Discussionmentioning
confidence: 88%
“…The strain-specific variations in astaxanthin content might stem from differential capacity in astaxanthin bioconversion and accumulation. The biosynthesis pathway of astaxanthin could involve many steps of enzymatic activities that produce a diverse groups of precursor metabolites (β-carotene, echinenone, and canthaxanthin), yet it is scarcely studied in copepod species 51 , 58 . In the future, the comparison of biosynthesize enzymes or relative gene expression levels between the two P. annandalei strains should be investigated using molecular biotechnology techniques, such as transcriptomic or metabolomic analysis, to uncover the molecular mechanisms that cause the variation of their astaxanthin concentration.…”
Section: Discussionmentioning
confidence: 99%